VD_FINDINFO Décision / 2015 / 848 vom 19. November 2015 - VD Tribunal cantonal (2015)
MESURE DISCIPLINAIRE, INTERDICTION DE L'ARBITRAIRE, DROIT CANTONAL, MOTIVATION DE LA DEMANDE | 91 al. 3 CP, 38 al. 3 LEP, 95 al. 1 LTF, 97 al. 1 LTF, 29 RDD